2014
DOI: 10.1016/j.cub.2014.03.042
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body Acoel Regeneration Is Controlled by Wnt and Bmp-Admp Signaling

Abstract: Whole-body regeneration is widespread in the Metazoa, yet little is known about how underlying molecular mechanisms compare across phyla. Acoels are an enigmatic phylum of invertebrate worms that can be highly informative about many questions in bilaterian evolution, including regeneration. We developed the three-banded panther worm, Hofstenia miamia, as a new acoelomorph model system for molecular studies of regeneration. Hofstenia were readily cultured, with accessible embryos, juveniles, and adults for expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
267
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(277 citation statements)
references
References 37 publications
10
267
0
Order By: Relevance
“…This is an intriguing issue, for it has been observed that acoels do not have, apparently, an obvious preference for ventral or dorsal NS localization. However, in a preliminary study, and in the context of animal regeneration, it has been shown that the acoel Hofstenia miamia have differential expression of BMPs (bone morphogenetic proteins) and their antagonistic ADMPs (anti-dorsalizing morphogenetic proteins) along this secondary axis [72]. How the expression of these genes is related to the position of the neurite bundles can be, at present, just a matter of speculation.…”
Section: Molecular Control Of Acoel Neurogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…This is an intriguing issue, for it has been observed that acoels do not have, apparently, an obvious preference for ventral or dorsal NS localization. However, in a preliminary study, and in the context of animal regeneration, it has been shown that the acoel Hofstenia miamia have differential expression of BMPs (bone morphogenetic proteins) and their antagonistic ADMPs (anti-dorsalizing morphogenetic proteins) along this secondary axis [72]. How the expression of these genes is related to the position of the neurite bundles can be, at present, just a matter of speculation.…”
Section: Molecular Control Of Acoel Neurogenesismentioning
confidence: 99%
“…Previous studies carried out by Srivastava et al [72] in H. miamia found five Wnt homologues which were branching together with one Wnt relative of the cnidarian Hydra vulgaris. We decided to try including those Wnt protein sequences in our analysis and see how they were placed in relationship to the Wnt relatives in our acoel species.…”
Section: A Genomics View Of Xenacoelomorpha Neurogenesismentioning
confidence: 99%
“…Thus, β-catenin acts as a master regulatory gene, responsible for the control of multiple processes. During early animal embryogenesis, β-catenin specifies the site of endoderm internalization and promotes posterior fates in most studied systems (Byrum and Wikramanayake, 2013;Darras et al, 2011;Haegel et al, 1995;Henry et al, 2008;Lee et al, 2006;Logan et al, 1999;Srivastava et al, 2014;Wikramanayake et al, 2003). In later stages of development, the canonical Wnt pathway influences the formation of multiple cell types, tissues and organ systems (Aulehla et al, 2008;Grigoryan et al, 2008;Hari et al, 2002;Holland et al, 2005;Kiecker and Niehrs, 2001; Lewis et al, 2004;Petersen and Reddien, 2009a;Schneider and Bowerman, 2007;Tan et al, 2006;Watanabe et al, 2014), and most prominently, the anteroposterior (AP) patterning of the vertebrate central nervous system (Ciani and Salinas, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…All the ML and Bayerian analyses, which used GTR or WAG models, displayed Acoelomorpha as the sister group to the rest of Bilateria, while the Bayesian tress generated using CAT or CAT+GTR models recovered paraphyletic deuterostomes and acoelomorphs as sister to protostomes (Table 1). Importantly, none of the analyses of Ryan et al (2013) or Srivastava et al (2014) showed Acoelomorpha as sister group or within Deuterostomia.…”
Section: A Contrasting Hypothesis: Acoelomorphs Are Deuterostomesmentioning
confidence: 99%
“…Finally, Srivastava et al (2014) published a study on the regeneration mechanisms of acoels which included extensive phylogenomic analyses focused on resolving the position of Acoelomorpha and Xenoturbella. All the ML and Bayerian analyses, which used GTR or WAG models, displayed Acoelomorpha as the sister group to the rest of Bilateria, while the Bayesian tress generated using CAT or CAT+GTR models recovered paraphyletic deuterostomes and acoelomorphs as sister to protostomes (Table 1).…”
Section: A Contrasting Hypothesis: Acoelomorphs Are Deuterostomesmentioning
confidence: 99%